2017
DOI: 10.26666/rmp.jesr.2017.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract:Egg is a universal food in our regular diet which rich in many nutrients. The purpose of this study was to calculate approximately the proximate nutritional content and assess the physical appearance in variety of duck eggs produced in Bangladesh. Eggs have been collected from four region representing different geographic areas in Bangladesh. Proximate nutritional value of eggs has been analyzed according to AOAC method. Antioxidant activity was determined by Yen and Chen method. Farm duck contains th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…In this study, the average shell thickness of the eggs collected from the breeders were similar to the results of previous studies (Carey et al 1990, Saatçi et al 2002, Tilki and İnal 2004, Ahmad et al 2017. However, studies in shell thickness in the rehabilitated breeds in Turkey is lower than that of native breeds.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the average shell thickness of the eggs collected from the breeders were similar to the results of previous studies (Carey et al 1990, Saatçi et al 2002, Tilki and İnal 2004, Ahmad et al 2017. However, studies in shell thickness in the rehabilitated breeds in Turkey is lower than that of native breeds.…”
Section: Resultssupporting
confidence: 90%
“…In studies investigating the factor effecting shell quality, the average shell thickness in geese was found to be around 0.44 -0.55 mm (Carey et al 1990, Tilki and İnal 2004, Ahmad et al 2017. Saatçi et al (2002) found the average shell thickness as 0.72, the highest as 0.94, the lowest as 0.45 and the precentage Coefficient of Variation (CV%) as 15.…”
Section: Introductionmentioning
confidence: 99%